Shear Strength Evaluation of Concrete Beams with FRP Transverse Rebar - Sakcali, Gokhan Baris; Yuksel, Isa (Budapest Univ Technology Economics, 2024)
Rebar corrosion in traditional reinforced concrete (RC) components may lead to a decrease in service life and carrying capacity. This condition is one of the reasons of the growing popularity of Fiber Reinforced Polymer (FRP) rebars as a corrosion-resistant alternative, particularly in RC infrastructure projects. Because the material properties and behavior of FRP rebar are very different from conventional steel rebar, the calculations used for reinforced concrete with conventional steel reinforcement should be updated for this material. The aim of this study is to propose a new shear strength prediction model for RC beams with transverse steel rebar in order to calculate the shear strength of RC beams with FRP transverse rebar according to TS-500, which is the Turkish Building Code. To achieve this goal, Finite Element Method (FEM) models were created for 27 RC beams with FRP transverse rebars and 9 RC beams without transverse rebars. Furthermore, for RC beams with FRP transverse rebars, a prediction model has been developed. Additionally, 13 prediction models obtained from regulations or scientific studies were compared to the proposed prediction model using a database of 105 tests obtained from previous experimental studies. It was observed that the proposed prediction model provides more consistent results with the test database from the literature compared to the models suggested by other regulations or studies. Therefore, by modifying the shear strength relations recommended in TS-500 for RC beams with transverse steel rebar, they can also be applied to RC beams with transverse FRP rebars.
Keywords: FRP rebars; RC beam; shear strength; stirrup